The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0102-311x2008000900017
|View full text |Cite
|
Sign up to set email alerts
|

Dor lombar em usuários de um plano de saúde: prevalência e fatores associados

Abstract: A cross-sectional study was conducted with individuals of both sexes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 26 publications
2
12
1
18
Order By: Relevance
“…Low back pain was the most frequent (40.0%; 95%CI 36.9 to 43.2) of those who referred pain. This prevalence is considered high and similar to those found in other studies [27][28][29][30] . A review study from the period of 1966 to 1988 describes the one-year prevalence of low back pain, ranging from 22% to 65% 31 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Low back pain was the most frequent (40.0%; 95%CI 36.9 to 43.2) of those who referred pain. This prevalence is considered high and similar to those found in other studies [27][28][29][30] . A review study from the period of 1966 to 1988 describes the one-year prevalence of low back pain, ranging from 22% to 65% 31 .…”
Section: Resultssupporting
confidence: 91%
“…A review study from the period of 1966 to 1988 describes the one-year prevalence of low back pain, ranging from 22% to 65% 31 . A recent research developed in the South of Brazil presented an one year prevalence of low back pain of 52.8% 30 , which is higher than the estimates observed in the present study. A study conducted in Germany, with workers, found an one-year prevalence of 60% of low back pain 29 .…”
Section: Resultscontrasting
confidence: 89%
“…A dor lombar apresenta etiologia multifatorial, incluindo fatores socioeconômicos e demográficos, estilo de vida urbano sedentário, obesidade, fumo, posturas viciosas durante o trabalho, aumento da sobrevida média da população e outros (3). Dentre os distúrbios dolorosos, a dor lombar constitui causa frequente de morbidade e incapacidade, sendo ultrapassada somente pela cefaleia (4).…”
Section: Introductionunclassified
“…In most cases, the lumbalgia is caused by mechanical problems in the joints and muscles. [6][7][8] In CrossFit training, individuals perform repetitive movements of lifting weights, squatting, and improper posture, 9,10 and an evaluation of whether these movements are being performed incorrectly during training, whether from carelessness or lack of guidance, is extremely important. These activities, when repeated frequently, can lead to spine problems and intense pain, especially in the lumbar region, where most of the weight is normally supported.…”
Section: Introductionmentioning
confidence: 99%